2012
DOI: 10.1063/1.4746785
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and magnetism in M(=IA, IIA)C compounds with the rocksalt structure

Abstract: Electronic structures of MC where M is the alkali and alkaline earth metals with the rocksalt structure are calculated by full potential density functional codes. We find that the spin magnetic moment in the compounds is mainly contributed by the spin polarized p-orbitals of carbon. The large distance between the carbon makes the p-orbitals localized, which induces magnetic instability according to the Stoner criterion. The electronic structure can be mapped to the rigid band model. SrC, BaC and RaC are half-m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
3
10
0
Order By: Relevance
“…As seen, the RbC is found to be semiconductor with fully spin polarized 2p states, whereas SrC is half-metal. These results are in good agreement with previous work on carbides compounds [15]. The total polarization of p-C states at the Fermi level demonstrates the sp-hybridization type.…”
Section: Structural and Electronic Propertiessupporting
confidence: 92%
See 1 more Smart Citation
“…As seen, the RbC is found to be semiconductor with fully spin polarized 2p states, whereas SrC is half-metal. These results are in good agreement with previous work on carbides compounds [15]. The total polarization of p-C states at the Fermi level demonstrates the sp-hybridization type.…”
Section: Structural and Electronic Propertiessupporting
confidence: 92%
“…This new class is based on alkali and alkaline earth metal elements, where the magnetic order is realized by the polarization of p-empty states without any direct contribution of d-electrons. Previous studies on alkali and alkaline earth metals with V-and VI-elements predicted half-metallicity with ferromagnetic order in various structures [5][6][7][8][9][10][11][12][13][14][15][16]. The total magnetic moment takes an integer value depending on the empty states at the Fermi level.…”
Section: Introductionmentioning
confidence: 99%
“…According to the studies undertaken in this field, these materials could be serious candidates in the spintronic field. Previous works cover binary compounds with V-and VI-elements and confirm half-metallicity with ferromagnetic ordering [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. In particular, carbon-based compounds exhibit ferromagnetism in various structures as binaries [6,9,12,14,16] and also as heusler-type structures [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…According to the paper of Zhang et al [16] and Lakdja et al [20], the SrC compound is found to be a half-metal, whereas the RbC compound is a semiconductor. There was suggested a possibility to have half-metallicity by doping alkali compounds with alkaline earth or vice versa [16]. This was the main source of motivation to study the Rb x Sr 1−x C alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a novel class of magnetic compounds containing neither transition metals nor rare‐earth elements, known as sp magnets, has been explored in the past several years. Ferromagnetic coupling was found in several binary I A –III A , I A –IV A , I A –V A , I A –VI A , II A –IV A , and II A –V A compounds with several simple crystalline phases such as rock‐salt, zinc‐blende, and wurtzite structures . The lack of experimental data in the case of these sp ‐magnetic compounds relates to the difficulties in fabricating such crystals.…”
Section: Introductionmentioning
confidence: 99%